Análise do uso e ocupação do solo e dos parâmetros físico-químicos da água na bacia hidrográfica igarapé Carrapato em Boa Vista, Roraima - Vieira, Arycélia da Silva (2022)
An important tool to remediate the damage caused in the Igarapé Carrapato hydrographic basin is the characterization of the use and occupation of only its polluting sources. It is fundamental or monitoring dessa bacia, because it is a very important bacia for the capital in all aspects, and using various tools, it was possible to do an integrated survey through the use of geotechnologies such as Remote Sensing, an indispensable tool not development of this research, which allows the automatic extraction of the hydrographic basin through satellite images and digital processing of the same. Foram used Landsat 8TM satellite images from the year 2020 and Google images from the year 2021, as well as the ArcGis 10.5 processing tool. The objective of this work is to assess the effect of the use and occupation of only the quality of the water in different points of the basin and also conduct or monitor two physical parameters of the water, analyzing the following parameters: pH, turbidity, dissolved oxygen, temperature, electrical conductivity, dissolved total solids and suspended total solids. The chemical parameters referring to the analyzes of this work, are rich in nitrite, nitrate, DBO and ammoniacal nitrogen. There are also collected water samples in two periods (summer and winter) and in 09 points along the course of the main water. Foram observed in the winter period the highest concentrations of ammoniacal nitrogen nutrient. And these can be associated with various sources, not only those that act directly in the basin, but also those that act in basins that are part of the complex of mixed springs. This information contributes significantly to the preliminary environmental diagnosis of the canals and becomes an important tool for the public power in its canal revitalization works in urban and rural areas, as well as for the scientific community.